2018
DOI: 10.1093/jas/skx022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of castration method and analgesia on inflammation, behavior, growth performance, and carcass traits in feedlot cattle

Abstract: Our objective was to determine the effect of castration timing, method, and use of the analgesic meloxicam (MEL) on inflammation, behavior, performance, and carcass traits in feedlot cattle. This study was a randomized complete block design conducted over a 3-yr period. In total, 194 crossbred beef calves from a single ranch origin were randomized at birth to receive one of five treatments arranged as a 2 × 2 + 1 factorial: 1) bulls castrated within 48 h of birth (CON), 2) bulls surgically castrated on day 0 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…Brown et al (2015) observed an increase in lateral lying duration in calves administered oral meloxicam; however, they could not identify if this change in behavior was related to pain or contentment. In contrast, Roberts et al (2018) did not find changes in standing or lying time among castration methods for the first 7 d after administration of an NSAID in weaned calves. However, Roberts et al (2018) found that a motion index indicative of the calf's pain response was reduced in surgical castrated animals administered oral meloxicam.…”
Section: Resultscontrasting
confidence: 70%
See 3 more Smart Citations
“…Brown et al (2015) observed an increase in lateral lying duration in calves administered oral meloxicam; however, they could not identify if this change in behavior was related to pain or contentment. In contrast, Roberts et al (2018) did not find changes in standing or lying time among castration methods for the first 7 d after administration of an NSAID in weaned calves. However, Roberts et al (2018) found that a motion index indicative of the calf's pain response was reduced in surgical castrated animals administered oral meloxicam.…”
Section: Resultscontrasting
confidence: 70%
“…In contrast, Roberts et al (2018) did not find changes in standing or lying time among castration methods for the first 7 d after administration of an NSAID in weaned calves. However, Roberts et al (2018) found that a motion index indicative of the calf's pain response was reduced in surgical castrated animals administered oral meloxicam. Similarly, Petherick et al (2014) observed that calves castrated at weaning and administered ketoprofen spent more time feeding and had reduced tail flicks compared with NM calves on the day of castration.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“… White et al (2008) observed increased standing time in surgically castrated beef calves relative to precastration standing using two-axis accelerometers. In yearling-age feeder cattle, Roberts et al (2018) also reported increased standing time in surgically castrated bulls vs. band-castrated bulls or steer controls. Petherick et al (2014) reported a tendency for surgically castrated mature bulls (i.e.…”
Section: Physical Behavior Monitoringmentioning
confidence: 85%